PENGARUH PENGGUNAAN CHAT GPT DAN LINGKUNGAN TEMAN SEBAYA TERHADAP HASIL BELAJAR SISWA KELAS XI MPLB MATA PELAJARAN KEPEGAWAIAN DI SMK KRIAN 2 SIDOARJO - Amanda Octavia, Gladis; Trisnawati, Novi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low cognitive learning outcomes of 11th-grade MPLB students at SMK Krian 2 Sidoarjo in the Civil Service subject, as evidenced by the large number of students scoring below the minimum passing grade (KKM). This situation is believed to be influenced by low motivation to learn, a less-than-conducive peer environment, and the suboptimal use of Artificial Intelligence (AI) technologies such as ChatGPT. This study aims to analyze the effect of ChatGPT usage, the peer environment, and the combined effect of both on student learning outcomes. This study employs a quantitative approach with an explanatory research design. The study population consisted of 156 11th-grade MPLB students, with a sample of 112 respondents selected using simple random sampling. Data were collected through observation, documentation of Mid-Semester Summative (STS) scores, and a Likert-scale questionnaire transformed using the Method of Successive Intervals (MSI). Data analysis was conducted using classical assumption tests and multiple linear regression with the aid of SPSS version 25.